Case Report: Acute Splenic Artery Thrombosis in a COVID 19, Postpartum Patient - Trancǎ, Sebastian Daniel; Antal, Oana; Farcaş, Anca Daniela (Frontiers in Medicine, 2021)
Abstract: The incidence of thromboembolic disease is reported to be high in SARS-CoV2 disease. Pregnancy, an already physiologically hypercoagulable state, associated to COVID 19, generates even more concern regarding the potentially increased risk of thrombotic events. The exact incidence of such complications is yet unknown, but there is data suggesting that coagulopathy and thromboembolism are both increased in pregnancies affected by COVID-19. Since the outbreak of the COVID 19 pandemics, the most common described thrombotic events associated with SARS-COV2 infection have been venous thromboembolism and disseminated intravascular coagulation, while arterial thrombotic events are less commonly described. Splenic infarction is a rare disorder that can be secondary to a hypercoagulable state. There are only few cases of splenic infraction described, but none with splenic artery thrombosis, in a post-partum patient, on therapeutic anticoagulation regimen. We present the case of a 31-year-old Caucasian, 26 weeks pregnant woman, with no prior medical history, admitted to the hospital with a severe form of COVID 19 pneumonia and who, during the course of the disease, developed a massive splenic infarction with splenic artery thrombosis.